PENERAPAN PENDEKATAN OPEN ENDED PROBLEMS DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 206 UJUNG BARU KABUPATEN SOPPENG - Awaluddin Muin (Publikasi Pendidikan, 2016)
The problems in this research is the lack of learning outcomes, especially in mathematics subject. The problem in this research is “How to applicate the open ended problems approach to improve mathematics learning outcomes in V grade 206 Ujung Baru Elementary School Districs Lilirilau, Soppeng?”. The purpose of this research is to describe the implementation of open ended problems approach to improve mathematics learning outcomes in V grade 206 Ujung Baru Elementary School Districs Lilirilau, Soppeng. This research use a qualitative descriptive approach with cyclicclassroom action research that includes planning, implementation, observation, and reflection. The focus of this research is the implementation and success of the open ended problems approach in mathematic teaching and learning process and also mathematics learning outcomes of the students class V. Subject in this research is V grade students in 206 Ujung Baru Elementary School totaling 10 students, consist of 7 female students and 3 male students who were active in the second semester of the school year 20015/2016. Data collection techniques in this research were the test, observation, and documentation. Data analysis techniques in this research were 1) data reduction, 2) data description, and 3) and deduction. The data in this research is the activities of teacher and students, and also students learning outcomes in mathematics subject. The result of this research shows the increase of the process and outcomes of mathematics learning in each cycle. The increasing of learning process and results can be seen from the 1” cycle to 2” cycle. Learning process and result 1” cycle is including sufficient qualification and then become better qualified on the 2” cycle. The conclusions of this research is the implementation of open ended problems approach can improve mathematic learning outcomes of the students class V 206 Ujung Baru Elementary School distric Lilirilau, Soppeng.Key Word: open ended problems approach, mathematics learning outcomes